Role of favipiravir in the treatment of COVID-19 (2020)
The COVID-19 outbreak all over the world has led the researchers to strive for developing drugs or vaccines to prevent or halt the progression of this ailment. To hasten the treatment process, repurposed drugs are being evaluated. Favipiravir is one such oral drug that was approved for new and re-emerging pandemic influenza in Japan in 2014 and has shown potent in vitro activity against SARS CoV-2. It has a wide therapeutic safety margin indicated by wide CC50/EC50 ratio for high dose. From the clinical studies in COVID-19, it has shown rapid viral clearance as compared to lopinavir/ritonavir and superior recovery rate than umifenovir. Overall, favipiravir has shown promising results in clinical studies in China, Russia, and Japan, and more trials are underway in multiple countries including USA, UK, India. Recently, treatment guidelines from many countries and some states from India have included favipiravir in the treatment protocol. This review provides insights on the evidence based evolving role of favipiravir in the management COVID-19 infection with emphasis on benefits of initiating an early antiviral therapy with special focus on favipiravir, its pharmacodynamic, pharmacokinetic, in vitro, clinical data and inclusion in the treatment protocols of COVID-19.